Second sound speed in a crystal of NaF at low temperature (Archives of Mechanics - Test, 1997)
We derive a physically justifiable model of heat conduction for rigid heat conductors based on a recent approach involving the gradient generalization of an internal state variable. The model accounts for observable phenomena in solid dielectric crystals, related to wave-like conduction of heat in certain ranges of low temperatures and a rapid decay of the speed of thermal waves close to a temperature value ϑλ, at which the conductivity of the material reaches a peak.